The roots of children‘s labour education in the history of pedagogics of Lithuania - Vasiliauskas , R. (Psichologija, 1972)
In the documents of the Party, in the works of scientific communism much place is devoted to labour training. Communist morality has formed out of folk’s moral norms. That’s why in the family of the Lithuanian peasant the child’s labour upbringing is very relevant nowadays as an important part of spiritual culture of Lithuanian folk. The peasant family has old traditions of labour training. They are testified by various sources such as folklore, ethnography, belles-lettres (works by Žemaitė, G. Petkevičaitė-Bitė, M. Valančius), memoirs of M. Katkus, S. Matulaitis, etc. The child’s labour education is considered folk pedagogics. In the second half of the nineteenth century folk pedagogics played quite an important role in education. Labour was one of the most important factors of education. As shown in the article, children’s labour training was conditioned both by pedagogical and social factors. Neither research work was carried out on folk pedagogics nor methodological problems discussed. So in the article different points of view of Soviet and foreign scientists on folk pedagogics are given. The aim of this research work is to show the role of labour training in the peasant family, to define the essence of upbringing, its features and methods, and to make some conclusions about progressive traditions of those times. Peasants’ reminiscences are one of the most important sources. For that purpose research methods such as questionnaires and interviews are used. At the end of the article some conclusions about the results of representative research are given.